2023
DOI: 10.1002/gps.5890
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level lithium in drinking water and subsequent risk of dementia: Cohort study

Abstract: Background Lithium, a mood stabilizer, is known to exhibit neuroprotective effects in animal models and may have anti‐dementia effects. Aims We used data from Scottish Mental Survey 1932, a population‐based cohort study, to investigate the association between lithium in drinking water and dementia rate in humans. Method Lithium levels in drinking water from 285 sampling sites across Scotland dating from 2014 were obtained from the sole public water provider (Scottish Water). Dementia and non dementia cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Even so, this exposure appears to maintain the potential to exert noticeable physiological effects (Harari et al 2015 ). A growing body of evidence suggests that exposure to sub-therapeutic lithium concentration through drinking water may impact a variety of clinically significant outcomes for the neuropsychiatric field, such as reducing dementia risk (Duthie et al 2023 ; Parker et al 2018 ), suicide risk (Barjasteh-Askari et al 2020 ), homicide risk (Giotakos et al 2015 ), psychiatric hospital admissions (Eyre-Watt et al 2021 ), but potentially increase autism spectrum disorder risk in prenatal exposure (Liew et al 2023 ). These data were further and robustly supported by a recent meta-analysis of 9 studies (Memon et al 2020 ), which suggested that naturally occurring lithium in drinking water may reduce the risk of suicide and possibly help in mood stabilisation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, this exposure appears to maintain the potential to exert noticeable physiological effects (Harari et al 2015 ). A growing body of evidence suggests that exposure to sub-therapeutic lithium concentration through drinking water may impact a variety of clinically significant outcomes for the neuropsychiatric field, such as reducing dementia risk (Duthie et al 2023 ; Parker et al 2018 ), suicide risk (Barjasteh-Askari et al 2020 ), homicide risk (Giotakos et al 2015 ), psychiatric hospital admissions (Eyre-Watt et al 2021 ), but potentially increase autism spectrum disorder risk in prenatal exposure (Liew et al 2023 ). These data were further and robustly supported by a recent meta-analysis of 9 studies (Memon et al 2020 ), which suggested that naturally occurring lithium in drinking water may reduce the risk of suicide and possibly help in mood stabilisation.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the interpretation of the available evidence appears particularly complex considering the difficulty in addressing possible confounders influencing the outcomes (e.g., socioeconomic factors on suicides), heterogeneity in the reported outcomes, sex differences in the observed associations, and the unfeasibility of assessing the amount of lithium exposure through routes other than drinking water (e.g., food) (Duthie et al 2023 ). Critical for the field is to define the impact of prenatal exposure to lithium in drinking water on fetal development, as past reports have suggested the potential for some health benefits, albeit non-unanimously, but also for possible detrimental effects (Harari et al 2015 ) even at comparatively similar concentrations (Eyre-Watt et al 2021 ; Liew et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, it has been reported that the concentration of lithium in drinking water is inversely correlated with not only the suicide rate (25, 26) but also the incidence of dementia (27,28). Other studies support an association between lithium levels in drinking water and the risk of dementia in females (29,30); however, a consensus has not been reached yet.…”
Section: Effect Of Lithium On Preventing Recurrence and Onset Of Deme...mentioning
confidence: 99%
“…Additionally, lithium levels in drinking water were associated with greater risk of dementia in women. 93…”
Section: Psychosocial Factors: Psychosocial Factors Such As Social Is...mentioning
confidence: 99%